2007
DOI: 10.1111/j.1742-1241.2007.01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria screening in patients with hypertension: recommendations for clinical practice

Abstract: Antihypertensive agents providing angiotensin II blockade are recommended for the treatment of hypertensive patients with microalbuminuria, regardless of diabetes and/or early or overt nephropathy. Treatment with angiotensin II receptor blockers provides effective reduction of microalbuminuria and blood pressure, and long-term prevention of CV events beyond blood pressure reduction. In addition, pharmacoeconomic studies have shown that these long-term benefits translate into a substantially reduced burden on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 84 publications
0
31
0
6
Order By: Relevance
“…Twenty-four-hour urine collection has long been regarded as the standard method as urinary albumin levels follow a circadian rhythm [21][22][23]. However, this method is associated with collection errors and lack of patient compliance [21][22][23]. Current recommendations included in the National Kidney Foundation Disease Outcomes Quality Initiative (DOQI), American Diabetes association, and ESH/ESC guidelines recommends measuring of urinary albumin : creatinine ratio (UCAR) [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four-hour urine collection has long been regarded as the standard method as urinary albumin levels follow a circadian rhythm [21][22][23]. However, this method is associated with collection errors and lack of patient compliance [21][22][23]. Current recommendations included in the National Kidney Foundation Disease Outcomes Quality Initiative (DOQI), American Diabetes association, and ESH/ESC guidelines recommends measuring of urinary albumin : creatinine ratio (UCAR) [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This is a simple, reliable and economic method which reportedly correlates well with cardiovascular risk [24]. Current recommendations indicate that MAU should be diagnosed on the basis of at least two out of three positive tests performed over a 3-6-month period, as single measurements might be false-positive due to physical exercise, actual blood pressure control, fever, and other factors [21][22][23]. However, if the first test is negative the test should be repeated only annually in at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing for microalbuminuria should probably be used more among COPD patient in the clinic. Interventions in microalbuminuria positive individuals with diabetes or hypertension are recommended and should include more aggressive treatment of cardiovascular risk factors like blood pressure, smoking, hyperlipidaemia and overweight [33][34][35]. So far, there are no recommendations for microalbuminuria screening in otherwise healthy people, although small studies have found a reduction in CVD by intervention with ACE inhibition [36].…”
Section: Discussionmentioning
confidence: 99%
“…Накапливаясь в тканях, КПГ приво-дят к образованию свободных радикалов кис-лорода и увеличивают окислительный стресс и модулируют эндотелий-зависимую СР. Взаи-модействие КПГ со своими рецепторами ведет к увеличению тромбомодулина и также активиру-ет рецепторы для интерлейкина-1, фактора не-кроза опухоли альфа (TNF-α) и ростовых фак-торов, что приводит к миграции и пролифера-ции гладкомышечных клеток и усилению пре-ссорной эндотелий-зависимой СР [23][24][25].…”
Section: Introductionunclassified